Factors affecting the demand of affordable housing among the middle-income groups in Klang Valley Malaysia - Zainon, N.; Mohd-Rahim, F.A.; Sulaiman, S.; Abd-Karim, S.B.; Hamzah, A. (University of Malaya, 2017)
Housing affordability has been a major concern issues in Malaysia especially those living in major cities like Kuala Lumpur and Selangor. Purchasing a “dream home” is one of those life accomplishments that top nearly everyone’s bucket list. Searching for a home comes with different considerations; housing market outcomes can be influenced by a range of different factors. In the long run. house prices will tend to converge to the cost of new housing construction. For that reason, this study aims to identify the determinants affecting the purchase decision among middle-income groups. The data was collected through questionnaire survey that was distributed in the Klang Valley area. The data was gathered then analysed using descriptive analysis and inferential statistical tests. Findings identified factors that have driven up the demand for housing, and in particular for home ownership, in recent years. It reveals that the affordable house price factor is the most important consideration in buying a house. This study would shed light for the developers in developing housing schemes based on the consumers1 preferences and could become a basis for the government to revise the current housing scheme policy’s design specifically in Malaysia.